Natural history as the foundation for researching plant-pollinator interactions: Celebrating the career of Marlies Sazima - Bergamo, Pedro J. [UNESP]; Agostini, Kayna; Machado, Isabel C.; van der Niet, Timotheüs; Maruyama, Pietro K. (Elsevier, 2024)
Pollination biology is anchored in natural history studies, defined broadly as the practice of observing and describing an organism's behaviour, interactions, and association with the environment in detail. Remarkable or unexpected observations of natural phenomena involving organisms are then interpreted in the light of prior knowledge. Valuing a variety of approaches to natural history studies from around the world, this Special Issue (SI) in FLORA brings together 29 articles to celebrate the career of Professor Marlies Sazima, who pioneered and influenced a generation of pollination biologists in Brazil. This collection puts together a mix of different studies, from detailed descriptions of the function of floral traits, pollinator foraging behaviour, and their effects on plant fecundity, to studies that scale up natural history information to untangle complex ecological patterns at the level of populations, communities or entire ecosystems. The SI also includes studies that make use of people's fascination with documenting natural phenomena, by using citizen science data as well as compiling data from the literature to produce comprehensive global reviews. We included studies with broad scopes and approaches on purpose, taking liberty with the definition of natural history, to highlight the fundamental practice of observing actual interactions between plants and pollinators in pollination biology studies, as well as to celebrate the diverse contribution made by Prof. Marlies throughout her career. We hope to continue mirroring her fascination with natural history and foster the next generation of scientists to carry on her legacy.
Keywords: Bats; Bees; Brazil; Hawkmoths; Hummingbirds; Pollination biology